Blockchain-Facilitated Cybersecurity for Ubiquitous Internet of Things with Space–Air–Ground Integrated Networks: A Survey - Wenbing Zhao; Shunkun Yang; Xiong Luo (Sensors)
This article presents a systematic review on blockchain-facilitated cybersecurity solutions for Internet of Things (IoT) devices in space–air–ground integrated networks (SAGIN). First, we identify the objectives and the context of the blockchain-based solutions for SAGIN. Although, typically, the blockchain is primarily used to enhance the trustworthiness of some systems or operations, it is necessary to document exactly in what context the blockchain is used that is specific to the IoT and SAGIN. Second, we investigate how blockchain technology is used to achieve the objectives. Again, we want to report the technical details on how blockchain is used in this specific field instead of general discussion. Third, we provide a critique on the technical correctness of the blockchain-based solutions. As we elaborate in this article, there are serious technical issues in the proposed solutions. The most pervasive assumption made in many blockchain-based solutions is that higher-level trustworthiness can be achieved by using any form of blockchain. Fourth, we provide a guideline on when blockchain technology could be useful for IoT and SAGIN and what types of blockchain could be useful to enhance the security of ubiquitous IoT in SAGIN.